Association between Serum Albumin Concentration and Ketosis Risk in Hospitalized Individuals with Type 2 Diabetes Mellitus - Po-Chung Cheng; Shang-Ren Hsu; Yun-Chung Cheng (Journal of Diabetes Research)
Objective. This study examined the association between serum albumin concentration and ketosis risk in hospitalized individuals with type 2 diabetes mellitus (T2DM). Methods. A retrospective cross-sectional study was conducted at a medical center in Taiwan. Inclusion criteria were endocrinology ward inpatients exceeding 21 years of age, with preexisting diagnosis of T2DM, and blood glucose above 13.9 millimoles per liter (mmol/L) at admission. Individuals without measurement of serum albumin, urine ketone, or hemoglobin A1C, or harboring active infection, myocardial infarction, cerebrovascular event, cirrhosis, malignancy, or overt proteinuria were excluded. Using serum albumin concentration below 3.0 grams per deciliter to define hypoalbuminemia, 151 hypoalbuminemic cases and 104 normoalbuminemic controls were enrolled. The presence of ketones in urine established ketosis. Results. The prevalence of ketonuria was 48% in hypoalbuminemic subjects compared to 30% in normoalbuminemic controls (odds ratio (OR): 2.15; 95% confidence interval (CI): 1.26–3.57; P=0.004). Moreover, among the 156 subjects with serum beta-hydroxybutyrate measurement in addition to urine ketone, 33% of the hypoalbuminemic individuals had ketonemia exceeding 3 mmol/L compared to 19% of those with normoalbuminemia (OR: 2.12, 95% CI: 0.99–4.48, P=0.051). Conclusions. Serum albumin concentration is inversely associated with ketosis risk in hospitalized individuals with T2DM.